Contribution to the study of the biochemistry of dystrophies and toxicosis: The serum proteins - Muñóz Pugliesevich, Julio (1940)
In Children's Medicine there are two disease entities, whose importance is considerable in our environment, and constitute one of the most difficult problems in pediatrics; we mean dystrophy and toxicosis